The Impact of Diversity, Equity, and Inclusion (DEI) Initiatives on Employee Performance - Rita Mulyanti; Tussoleha Rony, Zahara; Ali, Hapzi (Dinasti International Journal of Digital Business Management, 2024)
This study aims to understand the impact of Diversity, Equity, and Inclusion (DEI) initiatives on employee performance within organizations qualitatively using Systematic Literature. Diversity, Equity, and Inclusion within organizations have been proven through existing research with a correlation between variables and employee performance. This scientific article uses a structured literature review as its research approach. The literature review process involved the selection, identification, and analysis of relevant research publications. The PICO framework (Population/Problem, Intervention, Comparison, Outcome) was utilized to determine the study's scope by assigning scores to define research boundaries.  During the literature review, pertinent scientific publications were chosen, located, and examined. Scores were used to identify the study scope using the PICO framework. The study scope boundaries are listed in Table 1 along with reviews of the literature from other journals. Metrics from scientific journals are used in Table 2, which will be explained and provided with the results in this article.  The results show that DEI initiatives positively impact employee performance, with diversity enhancing creativity and innovation, and equity and inclusion improving employee morale and commitment.